Agricultural geography, issues and applications - Dube, R. S., 1941- (Delhi, India : Gian Pub. House, 1987)
Study covers Madhya Pradesh, 1956-1981.
Includes bibliographies and index.
mizan
Keywords: Agricultural geography -- India